Adalimumab Serum Concentrations, Clinical and Endoscopic Disease Activity in Crohn's Disease: A Cross-Sectional Multicentric Latin American Study - Letícia Rodrigues de Souza; Daniela Oliveira Magro; Fábio Vieira Teixeira; Rogério Serafim Parra; Eron Fábio Miranda; Omar Féres; Rogério Saad-Hossne; Giedre Soares Prates Herrerias; Renato Mitsunori Nisihara; Claudio Saddy Rodrigues Coy; Ligia Yukie Sassaki; Paulo Gustavo Kotze (MDPI AG, 2023)
Despite some variability in ideal serum Adalimumab (ADA) concentrations, there is increasing evidence that higher concentrations of anti-TNF-α agents can be associated with sustained efficacy, and low or undetectable levels may lead to loss of response. This study aims to correlate serum ADA concentrations with clinical and endoscopic activity in patients with Crohn's disease (CD). A cross-sectional and multicentric study was performed with patients with CD, who used ADA for at least 24 weeks. Patients were allocated into groups according to the presence of clinical or endoscopic disease activity. Serum ADA concentrations were measured and compared between groups. Overall, 89 patients were included. A total of 27 patients had clinically active CD and 62 were in clinical remission. Forty patients had endoscopic disease activity and 49 were in endoscopic remission. The mean serum ADA concentration was 10.2 μg/mL in patients with clinically active CD and 14.3 μg/mL in patients in clinical remission (p = 0.395). The mean serum ADA concentration in patients with endoscopic activity was 11.3 μg/mL as compared to 14.5 μg/mL in those with endoscopic remission (p = 0.566). There was no difference between serum ADA concentrations regarding clinical or endoscopic activity in CD, as compared to patients in remission